Approaches towards the synthesis of 5-aminopyrazoles - Aggarwal, Ranjana; Kumar, Vinod; Kumar, Rajiv; Singh, Shiv P. (Beilstein Journal of Organic Chemistry, 2011)
The biological and medicinal properties of 5-aminopyrazoles have prompted enormous research aimed at developing synthetic routes to these heterocyles. This review focuses on the biological properties associated with this system. Various synthetic methods developed up to 2010 for these compounds are described, particularly those that involve the reactions of β-ketonitriles, malononitrile, alkylidenemalononitriles and their derivatives with hydrazines, as well as some novel miscellaneous methods.
Keywords: alkylidenemalononitriles; 5-aminopyrazoles; hydrazines; β-ketonitriles; malononitriles